Յ. Կարստի «Միջին հայերենի բառարան»-ը հայ-իրանական լեզվական ուսումնասիրության սկզբնաղբյուր - Մ. Մալաք-Մոհամադի (ՀՀ ԳԱԱ Հ. Աճառյանի անվ. լեզվի ինստիտուտ)
Армяно-иранские и армяно-арабские культурные, экономические и литературные связи служили основанием для многих иранских и арабских заимствований в среднеармянском языке (XII-XVI вв.).The Armenian-Iranian and Armenian-Arab cultural, economic and literature ties haveserved as a basis for the linguistic correlations and numerous Iranian and Arab loanwords in Medieval Armenian (12th -16th centuries).
Keywords: Բառարան; Լեզվաբանություն